2019
DOI: 10.1103/physrevb.100.104302
|View full text |Cite
|
Sign up to set email alerts
|

Collective infrared excitation in rare-earth GdxLa1xB6 hexaborides

Abstract: Using Fourier-transform infrared spectroscopy and optical ellipsometry, room temperature spectra of complex conductivity of single crystals of hexaborides GdxLa1−xB6, x(Gd)= 0, 0.01, 0.1, 0.78, 1 are determined in the frequency range 30-35000 cm −1 . In all compounds, in addition to the Drude free-carrier spectral component, a broad excitation is discovered with the unusually large dielectric contribution ∆ε=5000 -15000 and non-Lorentzian lineshape. It is suggested that the origin of the excitation is connecte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 70 publications
2
7
0
Order By: Relevance
“…It was found recently that in the higher borides 3 RB 12 , development of the Jahn-Teller (JT) instability in the boron B 12 clusters leads to emergence of an infrared-active collective excitation that involves corresponding JT-mode, produces the rattling vibration of the RE atom and modulation of electronic density in the conduction band [11][12] . Very similar collective excitations were discovered in Gd x La 1-x B 6 as well [13] . It was suggested that they arise from the complex interaction among lattice, orbital and charge carriers subsystems, and that their striking consequence is the conversion, by virtue of collective interactions, of large fraction of conduction electrons into a non-equilibrium state with strong scattering.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…It was found recently that in the higher borides 3 RB 12 , development of the Jahn-Teller (JT) instability in the boron B 12 clusters leads to emergence of an infrared-active collective excitation that involves corresponding JT-mode, produces the rattling vibration of the RE atom and modulation of electronic density in the conduction band [11][12] . Very similar collective excitations were discovered in Gd x La 1-x B 6 as well [13] . It was suggested that they arise from the complex interaction among lattice, orbital and charge carriers subsystems, and that their striking consequence is the conversion, by virtue of collective interactions, of large fraction of conduction electrons into a non-equilibrium state with strong scattering.…”
Section: Introductionsupporting
confidence: 68%
“…It was suggested that they arise from the complex interaction among lattice, orbital and charge carriers subsystems, and that their striking consequence is the conversion, by virtue of collective interactions, of large fraction of conduction electrons into a non-equilibrium state with strong scattering. This phenomenon was also proposed [13] to cause a record low thermal emission work function of LaB 6 (φ≈2.66 eV [14] ).…”
Section: Introductionmentioning
confidence: 99%
“…When discussing the nature of (i) the large amplitude atomic displacements in GdB 6 , (ii) the formation of the dynamically coupled Gd-Gd dimers and (iii) the appearance of dynamic charge stripes at low temperatures observed in the present study for the first time, it is worth noting also the recent results of dynamic conductivity investigation of Gd x La 1-x B 6 [16]. In particular, it has been found in [16] that there are two components in the dynamic conductivity spectra, and, additionally to the contribution from Drude electrons a strong collective mode has been observed with a frequency of ~ 1000 cm -1 and with a damping of 2200 cm -1 (overdamped oscillator), which includes up to 70% of the conduction electrons available in these metals. The collective mode is typical for systems with cooperative dynamic Jahn-Teller (JT) effect in boron clusters [33][34] and in the case of GdB 6 it results from JT instability of B 6 molecules.…”
Section: Electronic and Lattice Instability In Gdbmentioning
confidence: 58%
“…1a) and a T-linear resistivity ρ(T) was opted to study fine details of the crystal and electronic structure, static and dynamic components of atomic displacement parameters and specific heat. Unlike some SCES located in the vicinity of QCP, GdB 6 is an antiferromagnetic (AF) metal (Néel temperature T N ≈ 16 K [15]), in which the majority of charge carriers (~70%) are non-equilibrium (hot) electrons, which participate in the formation of collective mode [16] already at room temperature. In the present study it is shown that dynamically coupled Gd dimers in combination with dynamic charge stripes are formed in GdB 6 with the temperature lowering (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that all these high borides are characterized by small enough residual resistivity values located in the range 0.01-50 Ohm•cm and their conduction band width is about 1.6-2 eV (see e.g. [28], [38], [39], [65], [86]), so the pseudogap may be considered as a merit of disorder and anharmonicity in these good metals.…”
Section: IVmentioning
confidence: 99%